Patterns of Political Communication in Virtual Leadership in Political Parties After the COVID-19 Pandemic - Septian, Esa; Wulandari, Septi (Universitas Medan Area, 2024)
After the COVID-19 pandemic, all sectors must still implement health protocols while continuing to work virtually to fulfill their obligations. The GERINDRA Party is one of the major parties in Indonesia that continues to carry out political communication to carry out its functions. The virtual leadership model and competitive organizational culture are applied in running an adequate organization. This research aims to analyze virtual leadership and competitive culture in post-pandemic organizations. The research method is carried out with bibliometric analysis which utilizes vos viewer software to conduct analysis and participatory research because the author is at the research location. The result is that virtual leadership is applied with several conditions, including leaders understanding the perceptions of members and organizations, leaders acting as the key to success, leaders being obliged to work remotely, leaders following the flow of globalization, and mastering ICT. Then the competitive organizational culture is applied with innovation, knowledge, collaboration, and target markets.